Ensuring Data Integrity in Cloud Storage: A Verifiable Approach with Outsourced Audits and Enhanced Performance - K Vivek Reddy; C. Shoba Bindu (Utilitas Mathematica, 2025)
The utilization of cloud storage has garnered significant attention from diverse users. Nevertheless, the separation of data management and ownership introduces potential security challenges, making it difficult to uphold data integrity. This study endeavours to conduct a thorough examination of the security issues inherent in cloud storage. Alongside establishing the verifiability of data updates, we present a novel method for conducting data integrity audits through outsourcing. This proposed approach caters to the requisites of both data confidentiality and verifiable data updates, eliminating the dependence on third-party entities. The escalating quantity of subfiles in cloud storage has a logarithmic impact on computational complexity. Subsequently, we have developed a prototype implementation that will undergo testing to assess its performance and underscore the advantages of our proposed methodology. The experiments conducted on this approach revealed its superior practicality and efficiency compared to preceding solutions.